Innovation, Total Factor Productivity (TFP) and Economic Growth In Indonesia: ARDL Bound Test Approach - Fajar Wijaya; Rahmatia Rahmatia; Nur Dwiana Sari (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aims to examine the cointegration relationship between innovation, TFP, and Indonesia's economic growth. The data used is secondary data in the form of a time series with a range of 1978–2019 sourced from WDI and PWT 10.0. The estimation technique uses the ARDL Bound Test Cointegration method. Empirical findings show that in the long term, innovation and TFP have a positive and significant influence on Indonesia's economic growth. In the short term, it is found that GDP lag-1, TFP, and trends have positive implications for driving Indonesia's economic growth. The balance of adjustments in the long term is shown from the ECT value, and based on the bound test, it is found that there is a long-term cointegration relationship.